"Reaching its limits": industry perspectives on salt reduction. Issue 7 (4th July 2016) - Lacey, Caron; Clark, Beth; Frewer, Lynn; Kuznesof, Sharron
Abstract : Purpose: – The purpose of this paper is to explore the barriers to, and implications of, salt reduction initiatives within the UK food manufacturing industry. Design/methodology/approach: – In total, 13 technical and new product development (NPD) managers were purposefully sampled from businesses supplying foods within the chilled convenience food sector. Data were generated using semi-structured interviews incorporating the critical incident technique. Thematic and comparative analyses identified similarities and differences in the challenges facing different product categories within the sector. Findings: – Barriers to further salt reduction included: manufacturing limitations; NPD constraints; food safety, quality and shelf-life trade-offs; and organoleptic acceptance. No single barrier dominated industry concerns and many barriers were interlinked. Overarching issues of competitive inequality between signatories and non-participants to voluntary salt reduction agreements, and the experience of product reformulation having reached its limits were prevalent. Originality/value: – This research provides a food industry perspective on the identified barriers faced by UK food processors and manufacturers in advancing salt reduction within the chilled convenience sector.